VIDEOGRAFI MAHASISWA BERBASIS TEAM BASED PROJECT PEMBELAJARAN BAHASA INDONESIA DI POLITEKNIK NEGERI SEMARANG: VIDEOGRAFI MAHASISWA BERBASIS TEAM BASED PROJECT PEMBELAJARAN BAHASA INDONESIA DI POLITEKNIK NEGERI SEMARANG - Rio Devilito; Puji Wahyumi; Sriwahyuningsih Sulaiman; Wildana Latif Mahmudi; Suroso (Politeknik Negeri Semarang, 2026)
Indonesian language learning at Semarang State Polytechnic is a means to develop students' language skills, both spoken and written. They are required to master soft skills in communication and teamwork as the main foundation before entering the workforce. The purpose of this study is to conduct real performance and optimize the competencies of Semarang State Polytechnic students to be creative and collaborative, maximizing language competence and working together with a team. The method used in this study is an exploratory study on Indonesian language learning and case studies on various activities carried out by students in producing videography worthy of appreciation. The data in this study are in the form of six videos recorded by students to demonstrate their competence in communication while showing the performance of their respective teams. The results of this study are that Semarang State Polytechnic students can improve the quality of the process and outcomes of Indonesian language learning because not only prioritize individual independent competence but learning is based on solid and comprehensive teamwork. Team-based projects can train students in problem management, train comprehension, and improve communication and collaboration skills with a team.